Capillary blood lactate concentrations during intermittent all-out exercise - Mognoni, P.; Redolfi, N.; Colombini, A.; Sirtori, M. S. (Journal of Sports Sciences, 1997)
The average maximal peak torques of the knee extensor and knee flexor muscles were measured during one, two or three series of 20 maximal contractions at an angular velocity of λrad s-1. Each series lasted about 20 s. After the first series, a 10 min rest was allowed before the second series of contractions. In one case only was a third series of contractions performed. Various sequences of contractions of the dominant and contralateral limbs were tested. Capillary blood lactate concentration ([LA]cap) was determined in the blood samples taken from an earlobe during each recovery. The difference between peak capillary blood lactate concentration and the concentration that would have occurred without any previous contraction (Δ[LA]cap) was taken as the index of metabolic comparison between the exercise bouts. The mechanical power output during the first series of contractions was similar to that in the second and third series, but the lactate elevation was significantly higher in the first series. The discrepancy between the constancy of the power output and the decrease in lactate elevation was even more evident if Δ[LA]cap was calculated as the difference between peak capillary blood lactate concentration and the value measured immediately before the second or third series. The decrease in lactate elevation was not affected by the change of the contracting limb from the first to the second series. In conclusion, the capillary blood lactate concentration profile during intermittent maximal exercise cannot be considered a suitable technique for evaluating lactate production.